Wetland and Stream Rapid Assessments Development, Validation, and Application - Dorney, John; Dorney, John; Savage, Rick; Tiner, Ralph W (Academic Press, 2018)
Wetland and Stream Rapid Assessments: Development, Validation, and Application describes the scientific and environmental policy background for rapid wetland and stream assessments, how such assessment methods are developed and statistically verified, and how they can be used in environmental decision-making$1 (Bincluding wetland and stream permitting. In addition, it provides several case studies of method development and use in various parts of the world. Readers will find guidance on developing and testing such methods, along with examples of how these methods have been used in various programs across North America. Rapid wetland and stream functional assessments are becoming frequently used methods in federal, state and local environmental permitting programs in North America. Many governments are interested in developing new methods or improving existing methods for their own jurisdictions. This book provides an ideal guide to these initiatives. - Offers guidance for the use and evaluation of rapid assessments to developers and users of these methods, as well as students of wetland and stream quality - Contains contributions from sources who are successful in academia, industry and government, bringing credibility and relevance to the content - Includes a statistically-based approach to testing the validity of the rapid method, which is very important to the usefulness and defensibility of assessment methodss